Managing social risk in China local administration: an examination of SSRA initiative - Liu, Zezhao (2018)
Social Stability Risk Assessment (SSRA) sponsored by the local administration is perceived as a socially defined risk-coping initiative since it became mandatory in China. This article observes and unravels SSRA practices by selecting Xuzhou municipality as a sample case. Findings show that local SSRA is operated by the tridimensional mechanism and antecedents of its effectiveness in enforcement are linked with multiple elements of administrative supports. The findings contribute to a full understanding of SSRA in mainland China where there is no electoral democratic regime, and provide implications for developing countries alike. Some recommendations are proposed as a potential driver of these results. - Reproduced.